Why the Future Might Actually Need Us: A Theological Critique of the ‘Humanity-As-Midwife-For-Artificial-Superintelligence’ Proposal. - Dorobantu, Marius (International Journal of Interactive Multimedia and Artificial Intelligence, 2021)
If machines could one day acquire superhuman intelligence, what role would still be left for humans to play in the world? The ‘midwife proposal,’ coming from futurists like Ray Kurzweil or James Lovelock, sees the invention of AI as a fulfillment of humanity’s cosmic destiny. The universe ‘strives’ to be saturated with intelligence, and our cyborg descendants are much better equipped to advance this goal. By creating AI, humans play their humble, but instrumental, part in the grand scheme. The midwife proposal looks remarkably similar to modern Christian anthropology and cosmology, which regard humankind as “evolution becoming conscious of itself” (Pierre Teilhard de Chardin), and matter as having a predisposition to evolve toward spirit (Karl Rahner, Dumitru Stăniloae). This paper demonstrates that the similarity is only superficial. Compared to the midwife hypothesis, Christian theological accounts define the cosmic role of humanity quite differently, and they provide a more satisfactory teleology. In addition, the scientific and philosophical assumptions behind the midwife hypothesis – that the cosmos is fundamentally informational, that it intrinsically promotes higher intelligence, or that we are heading toward a technological singularity - are rather questionable, with potentially significant theological and ethical consequences.